2002
DOI: 10.1002/ijc.10820
|View full text |Cite
|
Sign up to set email alerts
|

Geldanamycin decreases Raf‐1 and Akt levels and induces apoptosis in neuroblastomas

Abstract: Neuroblastomas are the most common extracranial solid tumors of childhood. These tumors are associated with an overall poor prognosis, particularly for advanced stage disease. The benzoquinone ansamycin antibiotic, geldanamycin (GA), exhibits potent antitumor activity in certain cancer cell lines by destabilizing important signal transduction proteins (e.g., Raf-1 and Akt). The purpose of our study was to determine whether GA can alter the expression of Raf-1 and Akt, which have been shown to be critical for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
43
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 48 publications
(52 reference statements)
8
43
1
Order By: Relevance
“…Because of its role in anti-apoptotic signaling, the Hsp90 client protein AKT was also selected for study as a potential marker of the activity of Hsp90 inhibitors in pediatric tumor cells. We were able to show marked decreases in levels of these proteins after GA exposure in all of the cell lines evaluated, and our findings are in agreement with those reported by Kim et al 50 regarding modulation of phospho-AKT levels in neuroblastoma cells after exposure to GA.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Because of its role in anti-apoptotic signaling, the Hsp90 client protein AKT was also selected for study as a potential marker of the activity of Hsp90 inhibitors in pediatric tumor cells. We were able to show marked decreases in levels of these proteins after GA exposure in all of the cell lines evaluated, and our findings are in agreement with those reported by Kim et al 50 regarding modulation of phospho-AKT levels in neuroblastoma cells after exposure to GA.…”
Section: Discussionsupporting
confidence: 93%
“…exposed to GA as a single agent, the IC 50 was 2.4 M. Because the ratio of GA to cisplatin was fixed at 1:100 when the drugs were used in combination, the GA concentration at the IC 50 for GA ϩ cisplatin was only 0.039 M. The addition of cisplatin thus resulted in a marked decrease in the IC 50 of GA in SAOS cells. Median dose analysis indicated that the combination of GA and cisplatin resulted in greater-than-additive inhibition of cell survival/proliferation as shown in Figure 4b.…”
Section: Greater Than Additive Inhibition Of Cell Survival/proliferatmentioning
confidence: 99%
“…Hsp90 inhibitor 17-AAG was a potent cytotoxic agent for human neuroblastoma NB69 cells, inducing cell death at concentrations ranging from 10 to 60 nM. These inhibitor concentrations were in the described range for SH-SY5Y cells (Kim et al 2003) and other tumor cell types with higher binding affinity to 17-AAG (Kamal et al 2003). Interestingly, proliferative spherical cells were significantly more sensitive to 17-AAG compared to differentiated flattened cells.…”
Section: Discussionmentioning
confidence: 92%
“…The figure is a representative result. The positions of relative molecular weight standards (in thousands) are indicated described as potent anti-tumor agents in certain tumor cells (Kamal et al 2003;Zhang et al 2007), including some human neuroblastoma cell lines (Kim et al 2003;Kang et al 2006), but the neuroblastoma NB69 cell line has not yet been studied. Hsp90 inhibitor 17-AAG was a potent cytotoxic agent for human neuroblastoma NB69 cells, inducing cell death at concentrations ranging from 10 to 60 nM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation